1999
DOI: 10.1002/(sici)1521-3773(19991004)38:19<2882::aid-anie2882>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of a Three-Dimensional [Ga6(L2)6] Metal-Ligand “Cylinder”

Abstract: A near trigonal antiprism with metal-metal distances in the nanometer regime is formed by the six metal ions in the crystalline, homochiral [Ga(6)(L(2))(6)] (see structure). This metal-ligand "cylinder" is based on a threefold symmetric, beta-diketone ligand, and represents a new geometry for metal-ligand clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 89 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…[8] An alternative strategy has been the design and preparation of complicated multidentate ligands favoring the assembly of metal ions into aggregates with topologies that may be anticipated from the structure of these ligands. This second course of action has led to the production of a large amount of polynuclear edifices displaying sophisticated shapes and architectures, such as helicates, [9] grids, [10] cylinders, [11] catenates, [12] and many more. Of these molecular species, only a minority have the metal ions disposed in close proximity so as to show cooperative effects resulting from strong magnetic-exchange interactions [13] or metalmetal bonding.…”
Section: (Py) 5 ] (1) Which Displays An Un-mentioning
confidence: 97%
“…[8] An alternative strategy has been the design and preparation of complicated multidentate ligands favoring the assembly of metal ions into aggregates with topologies that may be anticipated from the structure of these ligands. This second course of action has led to the production of a large amount of polynuclear edifices displaying sophisticated shapes and architectures, such as helicates, [9] grids, [10] cylinders, [11] catenates, [12] and many more. Of these molecular species, only a minority have the metal ions disposed in close proximity so as to show cooperative effects resulting from strong magnetic-exchange interactions [13] or metalmetal bonding.…”
Section: (Py) 5 ] (1) Which Displays An Un-mentioning
confidence: 97%
“…Raymond et al reported an M 6 L 6 trigonal antiprism complex from the combination of a C 3 -symmetric tris ¢-diketone ligand 5 3¹ and six-coordinate Ga III ( Figure 7). 27 In the [Ga 6 5 6 ] complex, three ¢-diketone binding sites of the ligand 5 3¹ are in different environments, and the whole framework has an idealized D 3 point group symmetry. Tris(¢-diketonato) Ga III units in one complex have the same optical isomerism, all-Δ or all-Λ (Figure 7b).…”
Section: ç Desymmetrization By Rigid Ligand Scaffoldsmentioning
confidence: 99%
“…In these processes, the formation of the desired products from the building blocks occur spontaneously and efficiently in one pot. For the spontaneous self-assembly of supramolecular coordination complexes including 1D-, 2D-, and 3D-network structures and grids, appropriate precursor building blocks are reacted in the presence of metal ions as templates [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%